The Quality of Eggs Derived from Japanese Quail Fed with the Fermented and Non-Fermented Rapeseed Meal - Karolina Wengerska; Anna Czech; Sebastian Knaga; Kamil Drabik; Tomasz Próchniak; Remigiusz Bagrowski; Angelika Gryta; Justyna Batkowska (Foods, 2022)
The most popular protein source in poultry feed mixtures is soybean. However, cheaper and more available alternative protein sources are being sought, and feed manufacturers more and more often turn their attention to the post-extraction meals of local oil plants, e.g., rapeseed. Therefore, the effect of fermented and non-fermented post-extraction rapeseed meal used as a feed additive for Japanese quails was investigated on the eggs’ quality. The study was performed on 280 females of Japanese quails fed with a mixture without rapeseed meal, with non-fermented post-extraction rapeseed meal (5%, 10% and 15%) and with fermented one (5%, 10% and 15%). During the experiment, eggs were collected from each group four times (every 4 weeks) and evaluated for their quality characteristics. The addition of 10% fermented rapeseed meal had the most beneficial effect on such eggs quality traits as egg weight, specific gravity, yolk index and color and albumen pH. However, in the majority of examined parameters, no significant differences were found between birds fed with soybean meal and those fed with fermented and non-fermented rapeseed meal (morphological elements proportions, yolk weight, albumen height and Haugh’s units, eggshell quality). This supports the thesis that the use of rapeseed meals instead of soybean meals may allow obtaining the proper quality of animal raw materials at a lower cost and with the use of local feed resources.